Identification of solid phase state of hemi-dihydrate atorvastatin in pharmaceutical raw materials - Madrigal Redondo, German (2015)
Determining the spatial configuration of the structures of compounds used in the production of medicines is extremely important due to the different characteristics of each of them in its solid state and therefore its different qualities of each for use as pharmaceutical raw material. This study aimed to identify the phase of the solid state of Atorvastatin hemi-dihydrate, a lipid-lowering medication HMG-CoA reductase widely use in the present and their characterization by four different instrumental analytical techniques: X-ray diffractometry, differential scanning calorimetry, thermogravimetry and infrared spectroscopy, comparing the obtained analytical results with those found in the literature. Using data obtained from these four techniques are able to show that the study sample exists predominantly in the 27 form of amorphic hemi-dihydrate calcic atorvastatin.